Analisis Promosi Melalui Market Place Shopee Dalam Peningkatan Penjualan Pt Angkasa Multitama Jakarta Selatan - Shihata Al Fajr Adhiimulloh; Surti Wardani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
. This research aims to analyze the promotion of the use of Shopee Onlineshop E-Commerce at PT Angkasa Multitama. This research is qualitative research with a descriptive approach. The data sources obtained are primary and secondary data. Data collection methods use interviews, observation and key informants. Researchers used triangulation from informants to draw data. The data analysis technique uses data from semi-structured interviews. The results of this research state that promotions based on attractive and good advertising can attract the hearts of consumers so that companies can increase their sales through the use of Shopee online shop E-Commerce. This is stated in several statements from informants that they need to improve their product copywriting and increase the supply of product stock. when the buyer experiences order broadcasting and uses advertisements optimally to get closure on every advertisement clicked by the buyer. Increasing human resources is also an evaluation for the owner to create increased sales because increasing human resources can help encourage promotions in order to increase sales for the company.